The spiritual forest: an ethnographic exploration of Finnish forest yoga and the forest landscape - Mäkelä Heidi Henriikka; Leiwo Lotta; Linkola Hannu; Rinne Jenni (Routledge, Taylor & Francis Group, 2025)
This article discusses the Finnish forest yoga phenomenon, which incorporates contemporary spiritual discourses on nature, landscape, ‘the self’ and gender. We scrutinise ethnographic fieldwork materials, autoethnographic writings and other materials related to forest yoga. By using the methods of collaborative ethnography, we assert that forest yoga practices partially question and fragment, and partially reconstruct, previous forest-related discourses, practices and imageries in Finland. This results in new interpretations of forest landscapes, in which the local, global and national scales are intertwined and mediated through the body and the experiences of the yogi in the forest space. In these processes, the forest becomes gendered as a feminine and ‘safe’ space for the female body, but it is also experienced as a place for negotiating metaphorical and physical ‘roots’. Thus, previous national discourses on forests as ‘sacred places of Finns’ are brought forth, but also reinterpreted in the transnational spiritual frame.